Immediate implant placement in the posterior mandibular region was assisted by dynamic real-time navigation: a retrospective study - Ningbo Geng; Jing Ren; Chi Zhang; Tianren Zhou; Chongjin Feng; Songling Chen (BMC, 2024)
Abstract Background Efficient utilization of residual bone volume and the prevention of inferior alveolar nerve injury are critical considerations in immediate implant placement (IIP) within the posterior mandibular region. Addressing these challenges, this study focuses on the clinical efficacy and implant accuracy of dynamic real-time navigation, an emerging technology designed to enhance precision in implantation procedures. Methods This study included 84 patients with 130 implants undergoing immediate placement in the posterior mandibular region. Stratified into dynamic navigation, static guide plate, and freehand implant groups, clinical indicators, including initial stability, distance to the inferior alveolar nerve canal, depth of implant placement, and various deviations, were systematically recorded. Statistical analysis, employing 1- or 2-way ANOVA and Student's t-test, allowed for a comprehensive evaluation of the efficacy of each technique. Results All 130 implants were successfully placed with an average torque of 22.53 ± 5.93 N.cm. In the navigation group, the distance to the inferior alveolar nerve and the depth of implant placement were significantly greater compared to the guide plate and freehand groups (P < 0.05). Implant deviation was significantly smaller in both the navigation and guide plate groups compared to the freehand group(P < 0.05). Additionally, the navigation group exhibited significantly reduced root and angle deviations compared to the guide plate group(P < 0.05), highlighting the superior precision of navigation-assisted immediate implant placement. Conclusions It is more advantageous to use dynamic navigation rather than a static guide plate and free-hand implant insertion for immediate posterior mandibular implant implantation.